Design of the Servo Control System of the Press Crimping Device based on Electronic Cam - Hui Li; Xiao Wu; Xu Wang; Xiao Qi; Liang Hua (Jixie chuandong)
Aiming at the working process of the press crimping device for paper tape crimping machine，on the basis of analyzing the movement process of the swing roller， the swing roller is regarded as the follower of cam mechanism. Its rotation angle is defined as equivalent to the stroke of the follower， and the action electronic cam curve of the swing roller is constructed. Thus， the control of the swing roller can be realized based on the electronic cam control mechanism. The definition of the electronic cam curve， especially the curve forms in the acceleration and deceleration area， and the angle relationship between the swing roller and the driving shaft in the acceleration and deceleration area are discussed in detail. It is concluded that the rotation angle of the driving shaft is twice as much as the rotation angle of the swing roller in the acceleration and deceleration area. Taking this as a guide， the parameters setting of the electronic cam function of servo motor are discussed， and it can be set off-line at different speeds of paper tape. Finally， the design idea of the PLC program to realize the above control is discussed and applied to the actual system. The reliability and stability of the press crimping device have achieved the desired effect.